SOSIALISASI DAN IMPLEMENTASI WAKAF PRODUKTIF DALAM RANGKA PEMBERDAYAAN MASYARAKAT DI DESA KALIULING, KECAMATAN TEMPURSARI, KABUPATEN LUMAJANG - Norma Ita Sholichah (JIK-PkM: Jurnal Inovatif dan Kreatif hasil Pengabdian kepada Masyarakat, 2023)
Law No. 41 of 2004 concerning Waqf is projected as a means of social engineering, making changes to the thoughts, attitudes and behavior of Muslims so that they are in line with the spirit of the law. One of the new regulations in the Waqf Law is productive Waqf. This article discusses the productive waqf in the perspective of Islamic economics and how the prospects are in empowering the economy of Muslims. Productive waqf is a scheme for managing waqf donations from the people, namely by producing these donations, so that they are able to produce a sustainable surplus. Productive waqf is not very familiar in the community, so it is necessary to socialize to the community about productive waqf and assist in the development and management of productive waqf, by conducting research that focuses on Krajan Hamlet and Tamansari Hamlet in Kaliuling Village, Tempursari District, Lumajang Regency. The community service activities aim to empower the people of Kaliuling Village through the implementation of productive waqf. This implementation will help the community manage village assets so that they can be maximized for common welfare. Apart from that, this effort also aims to educate the people of Kaliuling about the use of productive waqf as a source of mutual welfare. The dedication method used by researchers is a participatory action approach or commonly referred to as PAR (participatory action research). In the activity there are 3 main keys, namely the first identifying problems, planning problem solving, implementing, controlling and evaluating. The second is understanding, predicting, verifying, exploring, and so on. And the third is research, namely research activities in the academic world. This research activity is a critique of existing research paradigms, both positivistic and interpretive paradigms that are not concerned with social change. In the management and development activities of productive waqf in Kaliuling Village, Tempursari District, Lumajang Regency, it was carried out through several stages including; socialization of productive waqf to the community, forming management as Nadzir (manager) of Productive Waqf, recording data on waqf and goods being donated, as well as compiling administrative files for productive waqf management and pledges. The results of this activity are quite significant and can be understood by most of the Kaliuling village community, especially Dusun Krajan and Tamansari. This can be proven by the nadzir management in two (2) hamlets that have been formed, in Dusun Krajan there are 6 registered wakifs and in Dusun Tamansari there are 9 registered wakifs.